Avaliação da codigestão anaeróbia de resíduos alimentares e microalgas em um sistema integrado de tratamento - Luísa Ornelas Ferreira (2021)
Sustainable solutions for the treatment of food waste have become urgent in recent decades, since 1/3 of all food produced is wasted, emitting 3.3 billion tons of carbon dioxide equivalent. In view of the demand for an adequate management of these wastes, anaerobic co-digestion (digestion of two or more substrates) has been considered to improve the stability and methane production of the process, since food waste may present macro and micronutrients imbalance, low alkalinity and inadequate solids concentration, which can lead to digestion failure when mono-digested. In this context, the aim of this research is to evaluate the anaerobic co-digestion of food waste and microalgal biomass recovered in an integrated treatment system of food waste implemented at the Federal University of Minas Gerais, composed of an anaerobic reactor and a high rate algal pond (HRAP) for post-treatment of the digested effluent. For this purpose, biochemical methane potential tests (BMP) were evaluated to compare the mono-digestion of different food wastes treated in the system and, subsequently, the co-digestion between food waste and microalgae produced in the HRAP. Specifically, different proportions of both substrates and proportions estimating real scenarios in the integrated treatment system were tested. The results showed that mono-digestion of fruit and vegetables was inhibited (35 – 45 NmL CH4.g VS-1), probably due to acids accumulation, as was observed by low pH (4.9 – 5.3) and low methane content in the biogas (21 – 25%). The stabilization of the process was further attested by anaerobic co-digestion with microalgae, with the highest methane yield (514 NmL CH4.g VS-1) obtained at the 75:25 ratio of food waste and microalgae, based on volatile solids, with higher synergy between the substrates (28% higher compared to the calculated theoretical value). Estimates for real scenarios of co-digestion in an integrated system revealed that, due to the low microalgae production in the HRAP, as indicated in previous studies, 99:1 ratio would be more realistic if the totality of food waste and microalgae were considered. However, according to BMP tests, this proportion was inhibited, with an accumulated methane yield of 43 NmL CH4.g VS-1. Although a higher proportion of food waste in the mixture is preferable, a minimum amount of microalgae is needed to maintain process stability and increasing methane production. A second real scenario evaluated was the use of HRAP effluent to a minimum to dilute the food waste for a liquid digestion (15% total solids) without the addition of potable water. However, according to the results, this condition was also inhibited (49 NmL CH4.g SV-1), showing the need for other adjustments, such as the addition of alkalinity, trace elements or the increase in the proportion of microalgae in co-digestion.